Animated Videos in English Listening Skill Development - Dimas Agustiar Syah; Niko Fediyanto (Academia Open, 2026)
General Background: Listening is a core receptive skill in English language learning and remains challenging for EFL learners due to limited exposure, time constraints, and difficulties in processing spoken language. Specific Background: At SMA Negeri 1 Bangil, short instructional hours and the absence of varied digital media have constrained students’ mastery of listening, particularly in understanding procedure texts. Knowledge Gap: Although audiovisual media are widely discussed, empirical classroom-based evidence on the use of animated videos for senior high school listening instruction in time-limited contexts remains limited. Aims: This study aims to examine whether the use of animated videos as learning media supports students’ English listening skill development within restricted classroom time. Results: Using a quantitative pre-experimental one-group pre-test and post-test design with tenth-grade students, the findings show a statistically significant difference between pre-test and post-test scores, supported by normality testing and a paired sample t-test with a significance value of 0.000 (<0.05). Novelty: The study provides contextual evidence from a senior high school setting where animated videos had not previously been integrated into English instruction, addressing teacher concerns about practicality and classroom time limitations. Implications: The results suggest that animated videos can serve as a practical digital learning medium to support listening instruction, offering educators an alternative strategy for delivering procedure text material and managing limited instructional time in English language classrooms. Highlights: Statistically significant score differences were identified between assessments administered before and after the learning intervention. Quantitative testing confirmed that the collected data met normality requirements for hypothesis analysis. Classroom application demonstrated the feasibility of audiovisual materials under restricted instructional time conditions. Keywords: Animated Videos, Listening Skills, English Education, Procedure Text, Digital Learning Media